2011
DOI: 10.3892/ijo.2011.1073
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and carcinoma-associated fibroblasts sensitize breast cancer cells in 3D cultures to kinase inhibitors

Abstract: Abstract. Stromal cells, such as mesenchymal stem cells (MSCs) and carcinoma-associated fibroblasts (CAFs), play a role in cancer progression. To analyze their ability to modulate drug response, we generated spheroids of MCF-7 or MDA-MB-231 breast cancer cells in the absence or presence of human (h)MSCs or hCAFs and tested the susceptibility of the breast cancer cells to three different kinase inhibitors (TKI258, RAD001 and RAF265) used in cancer therapy. While stromal cells did not affect the response of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
(60 reference statements)
1
28
0
1
Order By: Relevance
“…Since then, several studies have shown that fibroblasts can induce resistance to various anticancer treatments, such as tamoxifen in the treatment of breast cancer (28,39), gemcitabine and radiotherapy in the treatment of pancreatic adenocarcinoma (26), and paclitaxel in the treatment of non-small cell lung cancer (30). Conversely, fibroblasts may also sensitize tumor cells to therapy as was shown for RAF and MEK1 inhibitors in breast cancer (33). However, the influence of CAFs on the cetuximab treatment response in HNSCC has not previously been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several studies have shown that fibroblasts can induce resistance to various anticancer treatments, such as tamoxifen in the treatment of breast cancer (28,39), gemcitabine and radiotherapy in the treatment of pancreatic adenocarcinoma (26), and paclitaxel in the treatment of non-small cell lung cancer (30). Conversely, fibroblasts may also sensitize tumor cells to therapy as was shown for RAF and MEK1 inhibitors in breast cancer (33). However, the influence of CAFs on the cetuximab treatment response in HNSCC has not previously been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs provide protumorigenic signals that lead to increased tumor growth via the stimulation of tumor cell proliferation and angiogenesis as well as the formation of metastases by the enhancement of the migratory and invasive potential of the tumor cells (18)(19)(20)(21)(22)(23)(24)(25). As a number of publications suggest that CAFs could also modulate the drug sensitivity of cancer cells (26)(27)(28)(29)(30)(31)(32)(33)(34), this study was undertaken to evaluate the influence of CAFs on the cetuximab response in HNSCC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…CAFs are the major cellular component of the tumor stroma and they have been shown to stimulate tumor growth, 188,194,195 EMT, 184,186,196,197 invasion, 198,199 and metastasis 196,200 and to influence treatment response, by secretion of soluble factors. [203][204][205][206][207][208][209][210][211] The detection of the soluble factors that are responsible for the influence on treatment response could lead to the development of new treatment strategies. However, the crosstalk between cancer cells and CAFs are still not completely understood and the nature of the soluble factors is largely obscure.…”
Section: Discussion Paper IVmentioning
confidence: 99%
“…Since then, numerous studies have shown that several different cell types within the tumor stroma, including CAFs, can influence the response to various anti-cancer treatments. [203][204][205][206][207][208][209][210][211] It is now clear that an abnormal stroma contribute to, or even is required for, tumor formation, progression, invasion, and resistance to anti-cancer treatments. 224 One huge disappointment within the stromal targeted therapy area is, as mentioned before, the failure of MPIs.…”
Section: Already In 1990mentioning
confidence: 99%
“…The report from the mixed 3D cultures with breast cancer cells and the MSC has proven the feasibility of the nodule growth in mixed setup [23]. Detailed analysis suggested that the MSCs rendered the breast cancer cells more susceptible to the kinase inhibitors in the 3D culture conditions.…”
Section: Discussionmentioning
confidence: 99%